Steady state analysis of gas networks with distributed injection of alternative gas. (15th February 2016) - Abeysekera, M.; Wu, J.; Jenkins, N.; Rees, M.
Highlights: A steady-state analysis method for gas networks was developed. This method is used for gas networks with distributed injection of alternative gas. A gas network with injection of upgraded biogas and hydrogen was simulated. Results show the impact on pressure and gas quality in the network. Abstract: A steady state analysis method was developed for gas networks with distributed injection of alternative gas. A low pressure gas network was used to validate the method. Case studies were carried out with centralized and decentralized injection of hydrogen and upgraded biogas. Results show the impact of utilizing a diversity of gas supply sources on pressure distribution and gas quality in the network. It is shown that appropriate management of using a diversity of gas supply sources can support network management while reducing carbon emissions.